Audiovisual quality assessment and prediction for videotelephony - Belmudez, Benjamin (T-Labs Series in Telecommunication Services,, 2015)
The work presented in this book focuses on modeling audiovisual quality as perceived by the users of IP-based solutions for video communication like videotelephony. It also extends the current framework for the parametric prediction of audiovisual call quality. The book addresses several aspects related to the quality perception of entire video calls, namely, the quality estimation of the single audio and video modalities in an interactive context, the audiovisual quality integration of these modalities and the temporal pooling of short sample-based quality scores to account for the perceptual quality impact of time-varying degradations.